Concise guide to computation theory - Maruoka, Akira (London, United Kingdom : Springer-Verlag, 2011)
This textbook presents a thorough foundation to the theory of computation. Combining intuitive descriptions and illustrations with rigorous arguments and detailed proofs for key topics, the logically structured discussion guides the reader through the core concepts of automata and languages, computability, and complexity of computation. Topics and features: presents a detailed introduction to the theory of computation, complete with concise explanations of the mathematical prerequisites; provides end-of-chapter problems with solutions, in addition to chapter-opening summaries and numerous examples and definitions throughout the text; draws upon the author$1 (Bs extensive teaching experience and broad research interests; discusses finite automata, context-free languages, and pushdown automata; examines the concept, universality and limitations of the Turing machine; investigates computational complexity based on Turing machines and Boolean circuits, as well as the notion of NP-completeness.s
pt. 1. The theory of computation -- pt. 2. Automata and languages -- pt. 3. Computability -- pt. 4. Complexity of computation -- pt. 5. Conclusions and exercise solutions.
Includes bibliographical references and index.
Keywords: COMPUTER SCIENCE